2016
DOI: 10.1002/smll.201503536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Nanoscale Gap Morphology on the Plasmon Coupling in Asymmetric Nanoparticle Dimer Antennas

Abstract: Coupling of plasmon resonances in metallic gap antennas is of interest for a wide range of applications due to the highly localized strong electric fields supported by these structures, and their high sensitivity to alterations of their structure, geometry, and environment. Morphological alterations of asymmetric nanoparticle dimer antennas with (sub)-nanometer size gaps are assigned to changes of their optical response in correlative dark-field spectroscopy and high-resolution transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…For predicting the properties of AuNP dimers, computer simulations usually employ a pair of gold spheres separated by a constant gap distance . In contrast to theory, the experimental realization of such an ideal dimer of spheres is challenging because of structural inhomogeneities: (i) uncontrolled gap distance at the scale of Ångströms; (ii) AuNPs prepared by conventional reduction chemistry are faceted, nonspherical nanocrystals; and (iii) multiple gap morphologies, i.e., different configurations of the opposing crystal facets in the gap region . The combination of all these structural inhomogeneities leads to plasmonic inhomogeneities of the corresponding dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For predicting the properties of AuNP dimers, computer simulations usually employ a pair of gold spheres separated by a constant gap distance . In contrast to theory, the experimental realization of such an ideal dimer of spheres is challenging because of structural inhomogeneities: (i) uncontrolled gap distance at the scale of Ångströms; (ii) AuNPs prepared by conventional reduction chemistry are faceted, nonspherical nanocrystals; and (iii) multiple gap morphologies, i.e., different configurations of the opposing crystal facets in the gap region . The combination of all these structural inhomogeneities leads to plasmonic inhomogeneities of the corresponding dimers.…”
Section: Introductionmentioning
confidence: 99%
“…The second issue, the nonperfect sphericity at the monomer level, has been solved in pioneering colloidal chemistry work using chemical etching yielding a smooth metal surface (Figure S2, Supporting Information) . The third issue, gap morphology, has recently been recognized as a decisive factor influencing the plasmonic properties of dimers or model system of dimers such as a particle on a mirror . However, it is currently not possible to experimentally control either gap morphology or to eliminate the influence of gap morphology in metal nanoparticle dimers.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, these observed variations in the far-field and near-field optical properties may have different origins. Particularly, the particle size, particle geometry and gap capacitor properties, such as, the gap size, the gap conductivity and the gap morphology are the most intuitive parameters, which have been shown to affect the LSPR position, width and scattering cross-section [18,25,28,36,5960]. As a first parameter, variations in the gap size have to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these NPs do not match with the shape of a perfect sphere used frequently for the simulations. Recently, it has been shown that the uniformity and size of the facets has strong influence on the homogeneity of their LSPR spectra [28,30,60]. From the high-magnification TEM images of the gap region of the dimers displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation